ANALISIS PERAN MODAL SOSIAL DALAM PENGEMBANGAN AGRIBISNIS TANAMAN HORTIKULTURA DI DATARAN TINGGI MALINO - Hasriliandi Halim; Makmur Mkmur; Ahmad Zailan; Adam Rahman Suradi (Fakultas Pertanian UST, 2026)
The development of horticultural agribusiness in highland areas is not determined solely by technical and economic factors, but is also strongly influenced by the social capital possessed by farmers. This study aims to analyze in depth the role of social capital in the development of horticultural agribusiness in the Malino highlands, Gowa Regency. The study employs a qualitative approach using a case study method. Data analysis was conducted using a thematic approach through the stages of data reduction, categorization, and conclusion drawing. The results indicate that social capital plays a significant role in the development of horticultural agribusiness. The element of trust is reflected in the fact that approximately 80% of farmers maintain marketing relationships with collectors without written contracts, yet these relationships remain stable and sustainable. This high level of trust reduces transaction costs, accelerates the sale of harvests, and lowers the risk of payment default. Other elements, such as social networks, also play an important role in expanding farmers’ access to production inputs and market information. Around 73% of informants stated that information on prices, seed availability, and fertilizers is obtained through farmer group networks and kinship ties. Farmers who are active in farmer groups demonstrate higher production cost efficiency, with average input cost savings of up to 15% through collective purchasing. Meanwhile, social norms such as mutual cooperation and deliberation remain strongly practiced, particularly in land preparation and harvesting activities. These practices are able to reduce labor costs by up to 20% and strengthen solidarity among farmers. Overall, social capital is proven to contribute to improved business efficiency, marketing stability, and the sustainability of horticultural agribusiness in the Malino highlands, Gowa Regency.